High School Students' Perceptions of Flipped Writing Instruction to Reduce Writing Anxiety - Nikita Syaza Filzah Prasetyo (Universitas Negeri Surabaya, 2026)
The aim of this research is to find out High school students' perceptions of Flipped Writing Instruction to reduce anxiety in writing and which of the four pillars of F-L-I-P is considered the most useful for reducing students' anxiety in writing. This research adopts a qualitative descriptive research method with a case study research design for analysis FWI user subjects with anxiety wrote better. Data obtained from that interview involve 15 12th grade students from one of the state high schools in Sidoarjo. Results of the interview stated that Most students have a positive perception of FWI caused and a small number have a negative perception. This positive perception includes two things: 1.) flexibility of space and time, 2.) learning specific material and 3.) reduction of burden and anxiety caused by group learning. Meanwhile, their negative perception shows that FWI does not have a significant effect on reducing anxiety in writing due to: 1.) inability to carry out independent learning, 2.) inactive study group performance, and 3.) lack of teacher feedback. In addition, the interview results stated that of the four pillars of F-L-I-P, what students considered to be the most helpful in reducing anxiety were pillars F and I, because flexibility and specific material adapted to students' learning conditions made students accustomed to building 'study' habits and preparing themselves before activities. in class, so their anxiety is much reduced.